Water and carbon fluxes in sprinkler irrigated winter wheat in North China Plain - Haijun Liu; Xueqing Zhou; Josef Tanny; Yuhui Ren; Xuyu Feng; Ronghao Liu (Agricultural Water Management)
Water and carbon fluxes are two vital ecological factors used for evaluating the sustainable development of farmland ecosystems, especially in water resources scarce regions. This study investigated the daily water and CO2 fluxes in four sprinkler irrigated winter wheat seasons using an eddy covariance system from 2019 to 2023 in the North China Plain (NCP) to quantify daily and seasonal field crop evapotranspiration (ETc act) and net CO2 exchange characteristics. Results show clear seasonal curves of water and CO2 fluxes in the winter wheat growth season. The seasonal crop ETc act under sufficient soil water conditions ranged from 393 to 456 mm with a mean value of 424 mm, and a seasonal crop coefficient of 0.79. The CO2 flux before winter showed emission from cropland to the atmosphere and was close to zero in the winter due to neglectable plant assimilation and much weak soil respiratory at low soil and air temperature. After re-greening in March, the CO2 flux showed uptake and reached its maximum in the middle of the grain-filling stage. At the later growth stage, emission of CO2 resumed. The seasonal net CO2 uptake is 41.93 103 kg ha−1, indicating a strong carbon sink. The equivalent CO2 in the dry biomass of wheat above ground surface at harvest was 31.18 103 kg [CO2.eq] ha−1 and accounted for 75 % of seasonal assimilated net CO2, indicating approximately 25 % of assimilated CO2 was stored in soil as root biomass and other soil organic carbon. Before winter, high soil temperature enhanced the CO2 emission, and high leaf area induced great CO2 assimilation after re-greening stage. The assimilated CO2 amount was linearly related to crop ETc act of 1–5 mm d−1, then reached saturation for ETc act higher than 5 mm d−1. Hence, maintaining crop evapotranspiration of approximately 5 mm d−1 at middle stage may induce higher water productivity in winter wheat croplands under sprinkler irrigation on NCP.